2016
DOI: 10.1038/srep23505
|View full text |Cite
|
Sign up to set email alerts
|

Crucial roles of XCR1-expressing dendritic cells and the XCR1-XCL1 chemokine axis in intestinal immune homeostasis

Abstract: Intestinal immune homeostasis requires dynamic crosstalk between innate and adaptive immune cells. Dendritic cells (DCs) exist as multiple phenotypically and functionally distinct sub-populations within tissues, where they initiate immune responses and promote homeostasis. In the gut, there exists a minor DC subset defined as CD103+CD11b− that also expresses the chemokine receptor XCR1. In other tissues, XCR1+ DCs cross-present antigen and contribute to immunity against viruses and cancer, however the roles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 55 publications
3
106
0
Order By: Relevance
“…While our manuscript was under review two studies found that CD103 + CD11b − DCs expand SI-LP Th1 cells during health, which supports our finding of functional specialization of these DCs for IFNγ + T cells (Luda et al 2016; Ohta et al 2016). IFNγ-inducing APC functions of CD103 + CD11b − DCs are also required for pathogen immunity and cytoprotection of intestinal epithelial cells (Mashayekhi et al 2011; Muzaki et al 2015).…”
Section: Discussionsupporting
confidence: 84%
“…While our manuscript was under review two studies found that CD103 + CD11b − DCs expand SI-LP Th1 cells during health, which supports our finding of functional specialization of these DCs for IFNγ + T cells (Luda et al 2016; Ohta et al 2016). IFNγ-inducing APC functions of CD103 + CD11b − DCs are also required for pathogen immunity and cytoprotection of intestinal epithelial cells (Mashayekhi et al 2011; Muzaki et al 2015).…”
Section: Discussionsupporting
confidence: 84%
“…This strain achieved nearly complete deletion in Langerhans cells and langerin + cDC1s in the dermis, skin-draining LNs, and lung. A second Cre line useful for targeting particular DC subsets is the Xcr1-cre strain, in which the first exon of the endogenous Xcr1 gene was replaced by c re (Ohta et al, 2016). This was crossed to Rosa26 -lacZbpA flox DTA mice (Brockschnieder et al, 2006), in which Cre excises a loxP flanked lacZ-polyadenylation (bpA) sequence and allows for DTA expression and cell ablation.…”
Section: Mouse Models For Studying Dendritic Cellsmentioning
confidence: 99%
“…However, a similar ablation of DCs did not always cause a disturbed homeostasis of peripheral T cells [66], possibly reflecting differences in deletion of specific DC populations in addition to complex physiologic conditions associated with the uptake of self-antigens and a subsequent activation of self-reactive T cells, as discussed above. Nevertheless, in other experimental systems including specific DTR expression in either chemokine receptor (XCR1) + DCs or in the entire DC lineage controlled by the transcription factor Zbtb46, as well as in experiments that relied on a chemical depletion of some DCs, the absence of DCs or their subsets disturbed tolerance and immune homeostasis [27, 28, 67]. …”
Section: Establishing the Roles Of Dcs As Key Inducers Of Peripheral mentioning
confidence: 99%
“…Subsequent studies found a substantial portion of the Foxp3 neg T cells that responded to DCs also converted into Foxp3-expressing peripheral regulatory T cells (pTreg cells) and documented the expansion of some pre-existing tTreg cells [68, 69]. Other studies found a similar extrathymic conversion by specialized CD103 + DCs presenting intestinal and food antigens within gut associated lymphoid tissues (GALT) of Foxp3 + Treg cells contributing to maintenance of local immune homeostasis [27, 28, 7073]. Recent results of experiments in an EAE model using Hopx −/− mice that have specific deficiencies in functions and survival of pTreg cells (but not tTreg cells) helped to further establish the essential roles of pTreg cells in the maintenance of DC-induced tolerance and prevention of organ-specific autoimmunity [54, 74].…”
Section: Exploring Tolerogenic Mechanisms Of Peripheral Dcs In Vivomentioning
confidence: 99%